Identification from a bitemark in a wad of chewing gum - Nambiar, P.; Carson, G.; Taylor, J.A.; Brown, K.A. (2001)
A wad of used chewing gum recovered from the scene of a burglary contained impressions of human teeth. Casts of these impressions displayed unique morphological characteristics which were found to show concordance with corresponding features present on casts of the posterior teeth of a suspect.